The Freiburg School and the Virginia School: introduction to the special issue - Lars P. Feld; Daniel Nientiedt (Public Choice, 2023)
This is the introduction to the special issue "The Freiburg School and the Virginia School: The Research Programs of Ordnungsökonomik and Constitutional Political Economy". It provides opening remarks and a brief overview of the individual articles.
Keywords: 330; Public Economics; Political Science